Recovery of cathode copper and ternary precursors from CuS slag derived by waste lithium-ion batteries: Process analysis and evaluation - Wei, Yun; Zhou, Lei; Hu, Wenbin; Yang, Liming; Yang, Guang; Wang, Chaoqiang; Shi, Hui; Han, Fei; Feng, Yufa; Ding, Xuan; Shao, Penghui; Luo, Xubiao (Chinese chemical letters, 2024)
The efficient and environmentally friendly recycling technology of waste residue that including abundant heavy metal produced during the recovery of lithium batteries has become a research hotspot. Herein, a novelty process of acid leaching-selective electrodeposition-deep impurity removal-regeneration was proposed to recovery of the CuS slag, which has been efficient transferred to high purity cathode copper and commercially available ternary precursors. Copper cathode with a purity of 99.67% was prepared under electrochemical reaction conditions at −0.55 V for 2 h. A novel impurity remover-Mn powder, which was used to remove the residual impurities and as a feedstock for the ternary precursor. Finally, NCM523 was regenerated by co-precipitation. The process is superior to the traditional process in economy, energy consumption, CO2 emissions, product purity and process duration. This study provides a new approach for solid waste recovery and precious metal enrichment. For the resourceful recovery of secondary waste from retired lithium-ion batteries, a novel process of acid leaching-selective electrodeposition-deep decontamination-regeneration was proposed to recover CuS slag, and regenerate it efficiently with high-purity cathode copper and commercially available ternary precursors. A new pathway for solid waste recovery and precious metal enrichment is provided. [Display omitted]